e-Learning diversification in higher education: conceptions of participation - Dias, Paulo (2020)
In this chapter, we reflect on the conceptions and different forms of participation in e-Learning contexts in higher education and its influences in climate change literacy. Although the literature review highlights intense research on the value of participation in informal contexts, we argue that the construction of a pedagogical discourse on e-Learning cannot be sustained without the pedagogy of participation. Such participation also acquires new meanings when analysed using socio-constructivist and cultural approaches. In this study, the analysis of participation in e-Learning contexts is based on categories such as leadership, sharing and cohesion. The empirical data we present are the result of more wide-ranging research carried out at the Observatório da Qualidade da Educação a Distância e e-Learning (Distance Education and e-Learning Observatory) at the Universidade Aberta, Portugal. Data were collected from the online questionnaire given to a sample of 26 e-Learning course leaders and pedagogical coordinators in face-to-face higher education institutions. The conclusions of the study highlight the different conceptions about the nature of e-Learning processes and practices in higher education, which we believe highlight the need to promote a participation-oriented pedagogy as a fundamental aspect of both climate change literacy/education and online education and based on the construction of both pedagogical innovation and teachers’ education to teach in virtual environments.